Quantum‐Confinement‐Enhanced Thermoelectric Properties in Modulation‐Doped GaAs–AlGaAs Core–Shell Nanowires. Issue 4 (9th December 2019) - Fust, Sergej; Faustmann, Anton; Carrad, Damon J.; Bissinger, Jochen; Loitsch, Bernhard; Döblinger, Markus; Becker, Jonathan; Abstreiter, Gerhard; Finley, Jonathan J.; Koblmüller, Gregor
Abstract: Nanowires (NWs) hold great potential in advanced thermoelectrics due to their reduced dimensions and low‐dimensional electronic character. However, unfavorable links between electrical and thermal conductivity in state‐of‐the‐art unpassivated NWs have, so far, prevented the full exploitation of their distinct advantages. A promising model system for a surface‐passivated one‐dimensional (1D)‐quantum confined NW thermoelectric is developed that enables simultaneously the observation of enhanced thermopower via quantum oscillations in the thermoelectric transport and a strong reduction in thermal conductivity induced by the core–shell heterostructure. High‐mobility modulation‐doped GaAs/AlGaAs core–shell NWs with thin (sub‐40 nm) GaAs NW core channel are employed, where the electrical and thermoelectric transport is characterized on the same exact 1D‐channel. 1D‐sub‐band transport at low temperature is verified by a discrete stepwise increase in the conductance, which coincided with strong oscillations in the corresponding Seebeck voltage that decay with increasing sub‐band number. Peak Seebeck coefficients as high as ≈65–85 µV K −1 are observed for the lowest sub‐bands, resulting in equivalent thermopower of S 2 σ ≈ 60 µW m −1 K −2 and S 2 G ≈ 0.06 pW K −2 within a single sub‐band. Remarkably, these core–shell NW heterostructures also exhibit thermal conductivities as low as ≈3 W m −1 K −1, about one order of magnitude lower than state‐of‐the‐art unpassivated GaAs NWs. Abstract : Modulation‐doped core–shell nanowires are demonstrated as promising nanothermoelectric to enhance thermopower while substantially inhibiting phonon transport. Using Si‐delta‐doped GaAs–AlGaAs core–shell nanowires the one‐dimensional sub‐band structure enables strong quantum oscillations in thermopower, and lattice thermal conductivities <3 W m −1 K −1 are found that are one order of magnitude lower than in state‐of‐the‐art unpassivated GaAs nanowires.